Locomotor Behaviour and Clock Neurons Organisation in the Agricultural Pest Drosophila suzukii - Hansen, Celia Napier; Özkaya, Özge; Roe, Helen; Kyriacou, Charalambos P.; Giongo, Lara; Rosato, Ezio (Frontiers in Physiology, 2019)
Drosophila suzukii (Matsumara) also called Spotted Wing Drosophila (SWD), is an invasive pest species originally from Asia that has now spread widely across Europe and North America. The majority of drosophilids including the best known Drosophila melanogaster only breed on decaying fruits. On the contrary, the presence of a strong serrated ovipositor and largely uncharacterised behavioural and metabolic adaptations allow D. suzukii to lay eggs inside healthy, ripening fruits that are still on the plant. Here we present an analysis of the rhythmic locomotor activity behaviour of D. suzukii under several laboratory settings. Moreover, we identify the canonical clock neurons in this species by reporting the expression pattern of the major clock proteins in the brain. Interestingly, a fundamentally similar organisation of the clock neurons network between D. melanogaster and D. suzukii does not correspond to similar characteristics in rhythmic locomotor activity behaviour.